The New Frontier: AI Population Health vs. Traditional Demographics in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of public health is undergoing a profound transformation, driven by the convergence of massive datasets and advanced computational power. For d...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine